Analysis of Factors Affecting Road Traffic Accidents in North Cyprus - Angın, M.; Albrka Ali, S. I. (Engineering, Technology & Applied Science Research, 2021)
Road traffic accidents are a global issue. North Cyprus exhibits a similar trend to the rest of the world. Urbanization and the increasing number of vehicles come along with the increase of road traffic accidents. The objectives of the current study are to draw attention to the issue of road traffic accidents and to identify which factors are the main causes of road traffic accidents in North Cyprus. This article follows a two-stage study to examine the causes of this critical issue. In the first stage, a survey was conducted to determine local public opinions. The participants were asked about how environmental factors, vehicle factors, human factors, and road factors impact accidents. According to the survey outcomes, human factors and road factors have the most significant impact. In the second stage of the study, official data from official statistics were considered. The number of accidents, fatalities, and injured people are indicated initially followed by the causes of accidents. Negligent driving and speeding were identified to be the most frequent causes within the studied period. At the end of the study, the common causes of accidents in official statistics and in survey results were specified. Negligent driving and over-speeding were the major causes of road traffic accidents according to the results.